(untitled) (Jurnal Teknologi (Sciences & Engineering), 2014)
Labu Sayong or also known as Labu Picit (pinched clay pitcher) is one of Malay potteries craft heritage originated from the state of Perak. This hand-crafted work has the specialties of its own. The stored water in the clay pitcher is colder than usual and it is believed that the water can refresh the body when consumed. Labu Sayong is an adaptation of a gourd and served as a symbol of intellectuals of the Malays in the past. It is produced through several traditional processes in stages and it takes some time to complete. This factor may cause its extinction. Therefore, many entrepreneurs have switched to a new innovation in the manufacturing process. Now, Labu Sayong has been produced by using moulds and it is called Labu Acu or cast clay pitcher. This innovation can produce commercialized product and the process is more productive than the traditional ways. To take these matters into consideration, the author used qualitative research method by using cultural approach in collecting written or visual data such as interviews and observation. An analysis of the technical aspects has found that the casting technique has successfully improved the quality and quantity of Labu Sayong which meets market demands. It is hoped this paper will give a certain amount of knowledge and facts that the manufacturing process of Labu Sayong is now going through a technological innovation. Innovation is crucial to ensure that Malay heritage will continue to exist and will never lost in the advanced technological era.